What are the driving factors behind the rise of spreads and CDSs of euro-area sovereign bonds? A FAVAR model for Greece and Ireland - Nicholas Apergis; Emmanuel Mamatzakis (Levy Economics Institute of Bard College, 2012)
This paper examines the underlying dynamics of selected euro-area sovereign bonds by employing a factor-augmenting vector autoregressive (FAVAR) model for the first time in the literature. This methodology allows for identifying the underlying transmission mechanisms of several factors; in particular, market liquidity and credit risk. Departing from the classical structural vector autoregressive (VAR) models, it allows us to relax limitations regarding the choice of variables that could drive spreads and credit default swaps (CDSs) of euro-area sovereign debts. The results show that liquidity, credit risk, and flight to quality drive both spreads and CDSs of five years' maturity over swaps for Greece and Ireland in recent years. Greece, in particular, is facing an elastic demand for its sovereign bonds that further stretches liquidity. Moreover, in current illiquid market conditions spreads will continue to follow a steep upward trend, with certain adverse financial stability implications. In addition, we observe a negative feedback effect from counterparty credit risk.
Keywords: C32; G00; G01; 330; Sovereign Debt Crisis; Spreads; CDS; FAVAR Model; Greece and Ireland